The Role of CO2-EOR for the Development of a CCTS Infrastructure in the North Sea Region: A Techno-Economic Model and Application - Roman Mendelevitch (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2013)
Scenarios of future energy systems attribute an important role to Carbon Capture, Transport, and Storage (CCTS) in achieving emission reductions. Using captured CO2 for enhanced oil recovery (CO2-EOR) can improve the economics of the technology. This paper examines the potential for CO2-EOR in the North Sea region. UK oil fields are found to account for 47% of the estimated additional recovery potential of 3739 Mbbl (1234 MtCO2 of storage potential). Danish and Norwegian fields add 28% and 25%, respectively. Based on a comprehensive dataset, the paper develops a unique techno-economic market equilibrium model of CO2 supply from emission sources and CO2 demand from CO2-EOR to assess implications for a future CCTS infrastructure. A detailed representation of decreasing demand for fresh CO2 for CO2-EOR operation is accomplished via an exponential storage cost function. In all scenarios of varying CO2 and crude oil price paths the assumed CO2-EOR potential is fully exploited. CO2-EOR does add value to CCTS operations but the potential is very limited and does not automatically induce long term CCTS activity. If CO2 prices stay low, little further use of CCTS can be expected after 2035.
Keywords: C61; L71; O33; 330